Building student employability through interdisciplinary collaboration: an Australian Case Study. Issue 3 (3rd July 2019) - Lin-Stephens, Serene; Kubicki, Josette M.; Jones, Fiona; Whiting, Martin J.; Uesi, John; Bulbert, Matthew W.
Abstract: Given that graduate employment is a clear outcome of education success, there is an urgent need to conceptualize course design strategically to maximize students' chances of employment. In this paper, we present an Australian case study in which we used a structured career information literacy learning approach to build employability in a biological sciences capstone course, through collaboration between the university library, academics, and career service. We report the context, method, measurement, outcomes of collaboration, and roles of contributors in this partnership. This case study lends itself to potential ways of incorporating career information literacy into an academic context.